Beyond the concept of cold and hot tumors for the development of novel predictive biomarkers and the rational design of immunotherapy combination. Issue 6 (18th February 2020) - De Guillebon, Eleonore; Dardenne, Antoine; Saldmann, Antonin; Séguier, Sylvie; Tran, Thi; Paolini, Lea; Lebbe, Celeste; Tartour, Eric
Abstract : Immunotherapy has revolutionized the management of cancers. At the end of 2018, 1, 716 clinical trials assessed regimen that combine program death‐1 (PD‐1)/program death ligand‐1 (PD‐L1) blockers with other cancer therapies (tyrosine kinase inhibitor, chemotherapy and radiotherapy). There is a contrast between these clinical dynamics and the difficulty of identifying biomarkers to better select patients that could benefit from immunotherapy. In this context, different tumor classifications have been proposed to try to better stratify patients. They rely on the characteristics of the tumor microenvironment and led first to divide them into hot and cold tumors. In this review, we aim to demonstrate the limitations of this classification focusing on the differential significance of subpopulations of intratumor CD8 + T cells. We also underline novel mechanisms of resistance to anti‐PD‐1/PD‐L1 blockade, focusing on myeloid cells, hypoxia and tumor immunoediting under treatment. Understanding the mechanisms of resistance to immune‐checkpoint inhibitor is indeed a powerful research driver that allows further identification of novel biomarkers, drug development and bring a rational to innovative therapeutic combinations.